ROLE OF INTELLECTUALS IN TRIBAL POLICIES OF REZA SHAH REGIME: A STUDY FOCUSING ON THE BAKHTIARI AND QASHQAEI TRIBE - Monirinejad, Mahdi; Heidari, Arman; Siahpour, Keshvad (Humanities & Social Sciences Reviews, 2020)
Purpose of the study: Following the entrance of Reza Shah into Iran’s political scene, the Persian archaist and nationalist intellectuals started to support him. These intellectuals believed that only through a central government with a Persian Nationalism could establish a united national nation-state in Iran. They played a key role in paving the path for the formation of a united nation-state and tackling the existing barriers before its path, e.g. the semi-autonomous traditional tribal governments, through establishing parties, societies, and newspapers and various activities in the administrative and bureaucratic domains. This is an issue which has not been discussed almost by no one of the scholars who have conducted studies on Iran. Methodology: The present study has been undertaken based on the method of historical sociology and through the use of the library sources. Results: In this way, the intellectuals who were supporters of the ancient Persian nationalism persuaded Reza Shah to adopt a radical military approach against the tribes. They consecrated Reza Shah and did not miss any opportunity to humiliate the tribes in every possible form. In fact, the pro-ancient Persian nationalism intellectuals had their own personal strategies for the destruction of the semi-independent governments. Applications of this study: This article plays a prefund role in studying the history of recent Iran. Novelty of the study: The Novelty of the study is in investigating the historical sociology and using various sources.